НУТҚ КАМЧИЛИГИГА ЭГА БЎЛГАН БОЛАЛАР ИБОРАЛИ НУТҚИНИ ХАЛҚ ЭРТАКЛАРИ АСОСИДА РИВОЖЛАНТИРИШ - Шакирова, С.Ю. (SCIENCE and SOCIETY, 2023)
In this article we are talking about the development of phraseological speech of children with speech defects based on folk tales, clarifying the psychological, pedagogical and methodological features of the speech development of children with speech defects of preschool age, the mechanisms of development of the connecting moment emphasized.